Bone mineralisation in premature infants cannot be predicted from serum alkaline phosphatase or serum phosphate. Issue 2 (1st September 2002) - Faerk, J; Peitersen, B; Petersen, S; Michaelsen, K F
Abstract : Background: The bone mineral content of premature infants at term is lower than in mature infants at the same postconceptional age. Serum alkaline phosphatase and serum phosphate are often used as indicators of bone mineralisation. Objective: To analyse the association between bone mineral content and serum alkaline phosphatase and serum phosphate. Methods: Serum alkaline phosphatase and phosphate were measured at weekly intervals during admission in 108 premature infants of gestational age below 32 weeks (mean (SD) gestational age 29 (2) weeks; mean (SD) birth weight 1129 (279) g). Bone mineral content was measured at term (mean gestational age 41 weeks) by dual energy x ray absorptiometry and corrected for body size. Results: Serum alkaline phosphatase was significantly negatively associated with serum phosphate (p < 0.001). Bone mineral content was not associated with mean serum alkaline phosphatase (p = 0.8), peak serum alkaline phosphatase (p = 0.5), or mean serum phosphate (p = 0.2) at term. Conclusion: Routine measurements of serum alkaline phosphatase and serum phosphate are of no use in predicting bone mineralisation outcome in premature infants.